The sonic boom : how sound transforms the way we think, feel, and buy - Beckerman, Joel. (Boston : Houghton Mifflin Harcourt, 2014)
"A surprising look at the hidden power of sound, revealing how people and brands can use it to inspire and persuade -- or annoy From horror movie scores to national anthems to the crunchy sound of potato chips, sound and music greatly impact how we feel about our lives and the messages and products we encounter every day. With the right tools and understanding, anyone can cut through the meaningless noise competing for our attention and learn to use sound as a rich storytelling strategy. You don't need to be a musician or a composer to harness the power of sound. Joel Beckerman explains how companies, brands, and individuals can strategically use sound to get to the core of their mission, influence how they're perceived by their audiences, and gain a competitive advantage. The key to these sonic strategies involves creating "boom moments" -- transcendent instants when sound connects with a listener's emotional core. The Sonic Boom draws surprising insights from real world examples: the way Disney parks score every second of their guests' experience; how Chili's restaurants uses lessons from evolutionary psychology to sell tons of sizzling fajitas, how the sound of a special edition Mustang's engine is designed to make drivers feel like action-movie heroes. Sure to appeal to fans of Made to Stick and This Is Your Brain on Music, The Sonic Boom offers readers a powerful new vocabulary for sharing impactful messages with sound"--
Introduction -- Night-vision goggles for your ears -- The boom moment -- Sonic landscapes -- The principles of sonic branding -- Rethinking possibilities -- Amplifying messages -- Scoring the experience -- Creating boom moments every day -- Hearing around corners.
Includes bibliographical references and index.
Keywords: Music -- Psychological aspects; Marketing -- Psychological aspects; Music in advertising; Sound -- Psychological aspects; BUSINESS & ECONOMICS / Marketing / General; MUSIC / Business Aspects; SOCIAL SCIENCE / General; Marketing -- Psychological aspects; Music in advertising; Music -- Psychological aspects; Sound -- Psychological aspects